Analisis Akomodasi Terhadap Minat Berkunjung Wisatawan Pantai Widodaren Yogyakarta - Lestari, Fitri Puji; Ananti, Deni Dwi (Jayapangus Press, 2023)
This research aims to provide a comprehensive analysis of the role of accommodation facilities in influencing tourists' interest in visiting Widodaren Beach. The results of the findings will certainly be used as additional in-depth insight into how to improve the tourism industry at Widodaren Beach. This research is quantitative research with variable X being accommodation. Meanwhile, variable Y is interest in visiting. The population in this data analysis is all visitors who visit this tourist attraction. The sampling technique uses accidental sampling or convenience sampling, which means that all visitors or anyone the researcher meets during observation are used as samples until the minimum criteria are met, namely 30 respondents. The results of this research are that there is a positive and significant relationship between accommodation quality and interest in visiting Widodaren Beach. If the quality of accommodation improves, it will also increase visitor interest in Widodaren Beach, Yogyakarta. Thus, efforts are needed from the management and local government to improve accommodation facilities at this tourist attraction.